Changes in the ionome of genetically modified corn plants with double-stranded RNA-suppressor of proline dehydrogenase gene - Schwartau, V.V.; Mykhalska, S.I.; Mykhalska, L.M. (Reports of the National Academy of Sciences of Ukraine, 2019)
The corn transgenic plant ionome with double-stranded (ds) RNA suppressor of the proline dehydrogenase ge ne obtained by the Agrobacterium-mediated transformation in planta plants of inbred line 370 of the Institute of Plant Physiology and Genetics NAS of Ukraine selection is studied. The analysis of seed T3 generation of corn plants with partial suppression of the activity of proline dehydrogenase and an increased resistance to the osmotic stress has shown differential changes of individual components of the ionome, namely: an increase in the content of Mg, Mn, Fe, Cu, and Mo, decreasing the content of Ca, K, and Na, and a significant reduction in the level of heavy metal ions: Ni, Ba, Cd, Sr. The growth of the content of the inorganic components of redox components, Mn, Cu, Fe, with the exception of Zn, is important for the formation of increased plant’s osmoresistance. It can be predicted that quantitative changes in the inorganic components of redox systems in genetically modified plants may be part of the increased resistance to osmotic stress. Increasing the resistance of corn will allow the introduction of mineral nutrition systems with high levels of assimilation of individual ions, which are based on the growth in local concentrations of individual elements and are characterized by increased levels of resistance to a moisture deficit. Reducing the content of a number of heavy metals in plants will allow the more extensive use of phosphorus fertilizers in the systems of nutrition that can be dangerous for soils and plants through the contamination by heavy metals.